ABILITY OF WRITING POETRY USING THE MEDIA PICTURE GRADE STUDENT VIII SMP 1 PSKD JAKARTA PUSAT - Rusmi siagian; Zainal Rafli; Siti Gomo Attas (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2020)
Abstract This research is a quantitative research that aims to describe the ability to write poetry based on the image media of students of class VIII SMP 1 PSKD JAKARTA PUSAT District. The population of this study consists of 151 students that are put into 5 classes. Sampling is done by using simple random sampling technique with total sample of 109 students. The instrument used is the test used to obtain the data of students' ability in writing poetry. The tests are given in the form of essays. Data analysis techniques used descriptive statistical analysis that describes the results of Writing Poetry Ability using Picture Media. Based on the descriptive statistic descriptive statistic analysis, the highest score obtained by the students in terms of the structure of the poem builder is 96 and the lowest score is 50 with the average score of 74,09. Thus it can be concluded that the students of grade VIII SMP 1 PSKD JAKARTA PUSAT are able to write poetry based on the media images. Keywords: writing, poetry, image media.